(3GdGMJQGS Yf fGQ GdfHQGSs - (3ESMGb Hf Ydj (B((3Gh eMeO(B) (3GdYHOj Gdjefj,J (B1115 (3g` s
(3ChdgG (B:s
(3GMeOc jG ef TjO GdGUhd GdOjf CSGSkG CeG HYO aEfi deG hbaJ Ydi GdfHQGS GdWGYf ai bhGYO GdGSGS s
(3BNQgG (B:s
(3hgPG GdLhGH VYja ceG HjfJg ai gGeT GdTQM GdePchQ hEf cGf eSJfOg ajg UMJgG hbO WGd GdeLGd hcKQ GdebGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdfSNI Hbde Hg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3eJaQbGJs